Plastic Bag Effect on Global Environment - Singh, Shikha (Journal of Advanced Research in Glass, Leather and Plastic Technology; Vol 3 No 1 (2020): Journal of Advanced Research in Glass, Leather & Plastic Technology, 2020)
Thousands of industries are producing plastic bags which are very popularly and commonly used for shopping because of its cheapness, ease, and accessibility of use. The plastic bags waste problem is gradually increasing in India and now has become an issue. Single use plastic bags litter our environment and require valuable resources to manufacture. The main objective of this research is to access different scenarios to control the use of plastic bags based on the socio-environmental impacts. Banning plastic bags might be a good example of fostering healthy lifestyles even though involving not so convenient shopping sundry activities. But the major issue here is the disposal of the plastic bags or in other words the last of proper disposal system. But the time is changing and now the people are aware of the side effects of improper plastic disposal. Not only they are reducing the use of plastic bags but also have started using the eco-friendly bags. According to the theory of green marketing, the customer or the stakeholder play a vital role in the environmental effects and health consciousness. The government of India banned the use of all kinds of plastic bags with some exemptions on 1 st August 2018. But here the common question arises that are the public willing and ready to come out of their comfort zone? If yes then what should be the alternative to the use of plastic bags?. India is a country where we have diverse human behaviour patterns. Here in my research, I have mainly focused on how to reduce the use of the over polluting plastic bags and what are the views and consequences the opinion of public on ban of plastics and the corresponding changes which can be implemented to reduce the same for the pollution free environment. How to cite this article: Singh S, Singh S. Plastic Bag Effect on Global Environment. J Adv Res Glass Leath Plast Tech 2020; 3(1): 10-13